Early interventionists' perceptions of supporting families experiencing poverty. Issue 13 (2nd October 2020) - Corr, Catherine; Milagros Santos, Rosa; Fowler, Susan A.; Spence, Christine; Skubel, Anna
ABSTRACT: A mixed methods design was used to facilitate an understanding of what early interventionists (EIs) experience when working with families living in poverty. EIs working in a large urban area ( n = 306) completed an online survey and participated in a follow-up focus group ( n = 7). EIs reported that logistical challenges and family/EIs stressors (e.g. domestic violence, personal safety concerns) impacted and often interrupted EI service delivery to families living in poverty. Implications for policy and professional development are described.